Pengaruh Tingkat Profitabilitas, Risiko Keuangan, Ukuran Perusahaan, dan Nilai Perusahaan terhadap Praktik Perataan Laba - Rastari, Rastari (Jurnal KIAFE, 2025)
This study examines the effects of profitability, financial risk, firm size, and firm value on income-smoothing practices in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2017–2021 period. The study employs a quantitative approach using secondary data obtained from annual financial statements. The sample was selected through purposive sampling and consisted of 12 companies, resulting in 60 initial firm-year observations. Companies were classified as income smoothers or non-income smoothers using the Eckel Index. After data transformation and outlier elimination, 46 observations were included in the final analysis. Profitability was measured using Return on Assets, financial risk was measured using leverage, firm size was measured using the natural logarithm of total assets, and firm value was measured using Price-to-Book Value. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 25. The results show that profitability has a negative and significant effect on income smoothing. Financial risk and firm size have negative but insignificant effects, while firm value has a positive but insignificant effect. Simultaneously, profitability, financial risk, firm size, and firm value do not significantly affect income smoothing. The adjusted coefficient of determination is 6%, indicating that the model has limited explanatory power.